(untitled) (Revista Cocar, 2018)
Este texto examina a configuração da profissão docente no sertão do São Francisco, a partir do depoimento de duas professores que atuaram em escolas primárias rurais nos municípios de Juazeiro-BA e Petrolina-PE, entre as décadas de 1950 e 1970. Desse modo, busca-se compreender nas memórias do passado as motivações para a escolha da profissão, bem como a complexidade e heterogeneidade das condições do trabalho docente. Em comum entre as duas professoras, destacam-se as precárias condições de trabalho, os baixos salários e ausência de residências anexas nas escolas. Por fim, tecemos algumas considerações sobre o processo da profissionalização docente e a emergência de estudos voltados à constituição da profissão no sertão pernambucano. Palavras-chave: Profissão docente. Professoras primárias rurais. Memória. Memories of rural primary teachers in the municipalities of Juazeiro-BA and Petrolina-PE (1950-1970) Abstract This text examines the setting of the" teaching profession in the backcountry of San Francisco, from the testimony of two teachers who worked in rural primary schools in the municipalities of Juazeiro-BA and Petrolina-PE, between the decades of 1950 and 1970. In this way, we seek to understand the past memories the motivations for choice of the profession, as well as the complexity and heterogeneity of work conditions. In common between the two teachers, the precarious working conditions, low wages and lack of attached residences in schools. Finally, we weave some considerations on the process of teacher professionalization and the emergence of studies aimed at the establishment of the profession in the sertão of Pernambuco. Keywords: Teaching profession. Rural primary teachers. Memory.